An analysis of creative thinking skills of biology education students at UIN Raden Intan Lampung - Puspita, Laila; Abdurrahman, Abdurrahman; Jalmo, Tri; Maulina, Dina; Rosiyanti, Anita; Komarudin, Komarudin (Indonesian Journal of Science and Mathematics Education, 2024)
Creative thinking is a crucial skill that involves generating and synthesizing new ideas by analyzing existing concepts and transforming them into innovative solutions. This ability is particularly important in education, where students must apply theoretical knowledge to real-world problems. However, not all students possess strong creative thinking skills. This study aims to analyze the creative thinking abilities of Biology Education students at UIN Raden Intan Lampung, focusing on 2021. The study evaluates students' creative thinking skills using Torrance's indicators: fluency, flexibility, originality, and elaboration. A qualitative descriptive approach was employed, with data collected through purposive sampling. The findings indicate that Biology Education students fall under the "quite creative" category. Specifically, fluency scored 57%, flexibility 48%, originality 43%, and elaboration 47%, all classified as "quite creative". The results suggest that while students demonstrate moderate creative thinking skills, there is room for improvement. Educators should integrate pedagogical strategies that enhance creativity, such as problem-based learning and open-ended assignments, to foster higher-level creative thinking in biology education. This study highlights the need for further targeted interventions to develop students' creative potential.